A Literature Review of the Economics of COVID-19 - Brodeur, Abel; Bhuyian, Suraiya; Islam, Anik; Gray, David (Université d'Ottawa | University of Ottawa, 2021)
The goal of this piece is to survey the developing and rapidly growing literature on the economic consequences of COVID-19 and the governmental responses, and to synthetize the insights emerging from a very large number of studies. This survey: (i) provides an overview of the data sets and the techniques employed to measure social distancing and COVID-19 cases and deaths; (ii) reviews the literature on the determinants of compliance with and the effectiveness of social distancing; (iii) the macroeconomic and financial impacts, including the modelling of plausible mechanisms; (iv) summarizes the literature on the socio-economic consequences of COVID-19, focusing on those aspects related to labor, health, gender, discrimination, and the environment, and v) summarizes the literature on public policy responses.
Keywords: 2103E; COVID-19; coronavirus; employment; lockdowns